A comparison of MOOC development and delivery approaches. Issue 2 (6th March 2017) - Smith, Neil; Caldwell, Helen; Richards, Mike; Bandara, Arosha
Abstract : Purpose: The purpose of this paper is to present a comparison of two ways of developing and delivering massive open online courses (MOOCs). One was developed by The Open University in collaboration with FutureLearn; the other was developed independently by a small team at the Northampton University. Design/methodology/approach: The different approaches had very different profiles of pedagogic flexibility, cost, development processes, institutional support and participant numbers. Findings: MOOCs on existing large platforms can reach thousands of people, but constrain pedagogical choice. Self-made MOOCs have smaller audiences but can target them more effectively. Originality/value: This comparison shows that, several years after MOOCs became prominent, there are many viable approaches for MOOCs.